2014
DOI: 10.1038/srep07383
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effects of short-wavelength visible light on insects

Abstract: We investigated the lethal effects of visible light on insects by using light-emitting diodes (LEDs). The toxic effects of ultraviolet (UV) light, particularly shortwave (i.e., UVB and UVC) light, on organisms are well known. However, the effects of irradiation with visible light remain unclear, although shorter wavelengths are known to be more lethal. Irradiation with visible light is not thought to cause mortality in complex animals including insects. Here, however, we found that irradiation with short-wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 33 publications
6
109
2
7
Order By: Relevance
“…Light is an important environmental signal for most insects192746. Light stress refers to the detrimental effect that exposure to insufficient or excess levels of light can have on an organism’s function and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light is an important environmental signal for most insects192746. Light stress refers to the detrimental effect that exposure to insufficient or excess levels of light can have on an organism’s function and development.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this phenomenon, several kinds of light traps have been used to monitor or reduce the populations of nocturnal insects, particularly noctuid moths1926. Artificial light can alter the habitat of nocturnal insects and disturb their normal behaviours, including flight, orientation, dispersal, migration, communication, foraging, mate recognition, oviposition, eclosion, and daily activity rhythms22232425, as well as affecting reproduction and populations of nocturnal insects by altering the night-time environment2728. As for other environmental factors, insects respond to artificial night-time light with an array of behaviours, and biochemical and genetic changes232729.…”
mentioning
confidence: 99%
“…Hori and colleagues revealed that blue light can kill some household pests and field crop pests (Hori et al, 2014; Hori and Suzuki, 2017). Insect species Drosophila melanogaster , Culex pipiens molestus , Tribolium confusum , and Galerucella grisescens , and wavelengths 407, 417, 438, and 465 nm were studied.…”
Section: Potential New Applications Of Antimicrobial Blue Lightmentioning
confidence: 99%
“…They prove that irradiation with short-wavelength visible light kills eggs, larvae, pupae and adult Drosophila. Studies conducted in this direction showed that high-toxic wavelengths of visible light have different degrees of toxicity for certain types of insects [5].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%